EVALUATION OF BRIDGE STRUCTURES USING ASSET SURVEY TECHNOLOGY TO BE USED AS MONITORING DATA (CASE STUDY: KAMOJANG HILL BRIDGE) - Armiati Ulfah; Ignatius Sudarsono; Robby Gunawan Yahya; Fauzia Mulyawati (LPPM Universitas Negeri Jakarta, 2023)
In the Bridge Management System (BMS92), monitoring is required to obtain information on the detection of early damage before the occurrence of more severe damage. Monitoring data requires a complete, accurate, and validated bridge structure evaluation data in the field. This study was conducted to evaluate the existing structure of the bridge using asset Survey technology (spesifically technology of Terrestrial Laser Scanning and aerial photogrammetry by UAV/Drone) to meet the needs of monitoring the factual condition of the bridge. This study was conducted in 4 stages, namely: preparation, 3d laser scanning onsite, 3d and 2d modeling, and data collection to evaluate the bridge structure. Method to evaluate the bridge structure by comparing the modeling data and existing data available (shop drawing). The monitoring are categorized into 4, namely: dimensions of the bridge elements, physical damage of the bridge elements, position changes of the bridge elements (deformation), and geometrical of the bridge. This study shows that (1) in some elements of the bridge there is mismatchs between dimensions of actual bridge with the dimensions in the shop drawing (2) There are three , physical damage of the elements (puddles in the connection that can lead to the corrotion, 80% of the bolts on the tied rod are rusty, and there are fragments of concrete on the abutment), (3) some elements/profiles are deformed even some elements/profiles exceed the deformation permit, and (4) the geometry of the bridge has a coordinate correction value with shop drawing